Creation of proportionality problems for the training of prospective primary school teachers - Burgos, María (2023)
[Objective] This article presents a description and analysis of an educational experience with prospective primary school teachers, aimed at developing their skills to create proportionality problems by modifying an initial problem to reflect a didactic-mathematical orientation. [Methodology] This is a qualitative and interpretative investigation that adopted an engineering or design approach to teaching in its research methodology. Theoretical and methodological tools of the Onto-semiotic Approach were used in both the design of the experience, and in the content analysis of participants’ responses. The investigation was carried out with a group of 127 Primary Education students of the University of Granada, Spain, organized in 33 teams to answer two problem-creation tasks. [Results] It was found that the participants most frequently created relevant problems by modifying a given problem, but that they did not manage to create problems that specifically allowed them to distinguish proportional from additive situations that are consistent with didactic-mathematical requirements. [Conclusions] Prospective teachers did not display sufficient didactic and mathematical knowledge to be able to successfully create proportionality problems. Training programs should therefore strengthen their strategies to develop this knowledge, incorporating it as a didactic resource in the teaching process to assist in improving the skills of prospective teachers in the analysis of mathematical activities.